Dynamic Reconfiguration of Security Policies in Wireless Sensor Networks - Pinto-Alarcón, Mónica; Gámez, Nadia; Fuentes-Fernández, Lidia; Amor-Pinilla, María Mercedes; Horcas-Aguilera, José Miguel; Ayala-Viñas, Inmaculada (My University, 2015)
Providing security and privacy to wireless sensor nodes (WSNs) is very challenging, due to the heterogeneity of sensor nodes and their limited capabilities in terms of energy, processing power and memory. The applications for these systems run in a myriad of sensors with different low-level programming abstractions, limited capabilities and different routing protocols. This means that applications for WSNs need mechanisms for self-adaptation and for self-protection based on the dynamic adaptation of the algorithms used to provide security. Dynamic software product lines (DSPLs) allow managing both variability and dynamic software adaptation, so they can be considered a key technology in successfully developing self-protected WSN applications. In this paper, we propose a self-protection solution for WSNs based on the combination of the INTER-TRUST security framework (a solution for the dynamic negotiation and deployment of security policies) and the FamiWare middleware (a DSPL approach to automatically configure and reconfigure instances of a middleware for WSNs).We evaluate our approach using a case study from the intelligent transportation system domain.
Keywords: Seguridad informática; FamiWare; INTER-TRUST; self-protection; self-adaptation; security frameworks; dynamic software product lines